The Federal Design of a Central Bank in Monetary Union: The Case of the European System of Central Banks - Sylvester C.W. Eijffinger (Oesterreichische Nationalbank (OeNB), 2002)
In this paper we analyse the ESCB as a federal central bank system. First, the degree of decentralization of the ESCB will be briefly compared with its predecessor, the Deutsche Bundesbank, and its counterweight in the US, the Federal Reserve System. Moreover, the development during the period 1990-99 of the total, economics and research staffing of the ECB and the national central banks in the EU will be investigated and also the staff ratios of the national central banks in 1999. Furthermore, the research activities of the central banks in the European Union over the period 1990-99 will be analysed both in terms of input (economics and research staff) and output (quaility-weighted number of articles in scientific journals). The share of economics research staff in total staff of the national central banks varies between 0.02 and 0.17. The ECB has the highest ratio between economists and researchers and other staff. A ranking of research performance based on the quality-weighted number of scientific articles per economics and research employee reveals that the Bank of Finland has the best research performance of European central banks, followed by De Nederlandsche Bank, the Banco de Portugal and the Oesterreichische Nationalbank. There is only a weak relationship between the research performance and the share of research staff. The conclusion small is beautiful also seems to hold for the economics and research departments of the European central banks.
Keywords: 330